2008
DOI: 10.1016/j.automatica.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental limitations in control over a communication channel

Abstract: Fundamental limitations in feedback control is a well established area of research. In recent years it has been extended to the study of limitations imposed by the consideration of a communication channel in the control loop. Previous results characterised these limitations in terms of a minimal data transmission rate necessary for stabilisation. In this paper a signal-to-noise ratio (SNR) approach is used to obtain a tight condition for the linear time invariant output feedback stabilisation of a continuous-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 10 publications
1
64
0
Order By: Relevance
“…The proof of (7) is given in [17] and is included in the Appendix 1 for completeness. Formula (7) presents explicitly the main obstacles to feedback stability in terms of a limitation in the channel SNR, that is: unstable poles, NMP zeros and time delay.…”
Section: Powmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof of (7) is given in [17] and is included in the Appendix 1 for completeness. Formula (7) presents explicitly the main obstacles to feedback stability in terms of a limitation in the channel SNR, that is: unstable poles, NMP zeros and time delay.…”
Section: Powmentioning
confidence: 99%
“…The analysis introduced in [15,16] considers an additive white Gaussian noise (AWGN) channel model, casting the stabilisability problem of a linear time invariant (LTI) unstable plant as one of lower bounding the channel signal-to-noise ratio (SNR). In [17] we extended the formulation of [15,16] to the case of an additive coloured Gaussian noise (ACGN) channel with a bandwidth limitation. Such bandwidth limitation may be imposed, for example, to avoid interference between different channels, while the coloured noise assumption is more realistic for a general communication channel.…”
Section: Introductionmentioning
confidence: 99%
“…In these papers, the minimum signal-to-noise ratio (SNR) of Correspondence to: Reza Mahboobi Esfanjani, E-mail: mahboobi@sut.ac.ir channel required for stabilizability of the system was obtained in terms of the plant's unstable poles and nonminimum phase (NMP) zeros. Similar problem was solved in [17], where the communication medium is an additive colored Gaussian noise channel with finite bandwidth. Utilizing an output feedback controller, it was shown that the bandwidth limitation of channel leads to greater minimum SNR required for stabilization than the one obtained in [16].…”
Section: Introductionmentioning
confidence: 93%
“…Owing to using a frequencyselective notion of SNR, the problem was solved in a simpler way than the similar one in [17]. The presented stabilizability threshold includes NMP zeros of the channel besides its other factors and consequently the effect of these zeros on system stabilizability was shown for the first time.…”
Section: Introductionmentioning
confidence: 97%
“…Among several research directions on this topic, a great deal of attention has been given to the case when the communication channels can be modeled as additive white gaussian noise (AWGN) channels [1]. The issue of time delay has been addressed in [2], the encoder/decoder design has been addressed in [3], and the disturbance rejection has been studied in [4].…”
Section: Introductionmentioning
confidence: 99%